Dampak pencemaran air sungai Kahayan pada usaha budidaya ikan karamba di Kelurahan Pahandut Seberang Kota Palangka Raya. - Nyata Susila (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
This study aims to assess the impact of water pollution on cage aquaculture owned by farmers in watersheds Kahayan, especially those in Village Pahandut Seberang, Palangka Raya city. The study used a survey method that was implemented in September 2014. The results showed that some water quality parameters exceed the predetermined threshold. The death of fish in cages often occurs when change of water patterns on June to September where turbidity of the water is very high, a slow stream, and ammonia poisoning the fish cultivated. Key words : Water pollution, Kahayan River, cage aquaculture.